1995
DOI: 10.1155/1995/271936
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Treatment of Immigrants and Refugees to Canada for Tuberculosis: Implications of the Experience of Canada and other Industrialized Countries

Abstract: Data synthesis led to the conclusions that immigrants and refugees to Canada have five times the nonimmigrant and non-Aboriginal rate of tuberculosis; that screening programs discover new cases of tuberculosis on and after arrival and that up to 20% of those scheduled to attend a tuberculosis clinic after arrival may never attend; that drug resistance is widespread in countries from which Canada receives immigrants; and that directly observed therapy for active cases can result in 100% conversion rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…They included two guidelines from the United States that addressed screening for latent tuberculosis infection in immigrants, 5,6 three articles that addressed tuberculosis screening issues in foreign-born patients, [7][8][9] one review of postlanding surveillance in Canada, 10 and three narrative reviews of screening immigrants and refugees that recommended screening for latent tuberculosis infection in immigrants and refugees, but none used a systematic review method. [11][12][13] In the search for systematic reviews and guidelines for research involving the general population and tuberculosis, 3968 articles were identified, and 18 met the eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They included two guidelines from the United States that addressed screening for latent tuberculosis infection in immigrants, 5,6 three articles that addressed tuberculosis screening issues in foreign-born patients, [7][8][9] one review of postlanding surveillance in Canada, 10 and three narrative reviews of screening immigrants and refugees that recommended screening for latent tuberculosis infection in immigrants and refugees, but none used a systematic review method. [11][12][13] In the search for systematic reviews and guidelines for research involving the general population and tuberculosis, 3968 articles were identified, and 18 met the eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Of all immigrants screened for tuberculosis before immigration, less than 1% are found to have active tuberculosis, and 3%-5% (8000-13 000 people/yr) are found to have inactive tuberculosis. 2,9 Despite forming a high-risk group for active tuberculosis, they account for only a small proportion of all cases of tuberculosis in the foreign-born population (8% in a study in Alberta), which could in part be due to program limitations. 107,[124][125][126] All the domestic screening programs (school-based, targeted immigrant or refugee, or contact tracing) for latent tuberculosis infection perform suboptimally; only about 47% (range 11%-72%) of people with positive results of tuberculin skin tests actually complete treatment.…”
Section: Reviewmentioning
confidence: 99%
“…If radiographic abnormalities are detected, the affected individual is referred, usually to a chest specialist, for further evaluation, including additional radiographic, microbiologic (e.g., sputum acid-fast bacilli), and tuberculin tests when judged appropriate. Medical evaluation is performed wherever the application is made, in the applicant's country of origin or in Canada (15). Since mid-1995, all immigrants from within the greater Montreal area who have applied for permanent residence have undergone screening chest radiography at the MCI.…”
Section: Setting and Study Cohortsmentioning
confidence: 99%
“…When they arrive in Canada, immigrants or long-term visa-holders in whom inactive TB is detected (equivalent to the U.S. Immigration and Naturalization Service classification of "B2" [12]) during the medical evaluation done as a part of preimmigration screening are referred by Citizenship and Immigration Canada to provincial health authorities for medical surveillance (15). Since 1994, the Montreal Public Health Department is notified of all immigrants arriving in Quebec who require surveillance for inactive TB, and it refers those who are resident on the island of Montreal to the MCI.…”
Section: Setting and Study Cohortsmentioning
confidence: 99%
See 1 more Smart Citation